Insight on Shallow Trap States-Introduced Photocathodic Performance in n-Type Polymer Photocatalysts - Ruan, Qiushi (J Am Chem Soc, 2020)
[Image: see text] Graphitic carbon nitride (g-C(3)N(4)) is a robust organic semiconductor photocatalyst with proven H(2) evolution ability. However, its application in a photoelectrochemical system as a photocathode for H(2) production is extremely challenging with the majority of reports representing it as a photoanode. Despite research into constructing g-C(3)N(4) photocathodes in recent years, factors affecting an n-type semiconductor’s properties as a photocathode are still not well-understood. The current work demonstrates an effective strategy to transform an n-type g-C(3)N(4) photoanode material into an efficient photocathode through introducing electron trap states associated with both N-defects and C–OH terminal groups. As compared to the g-C(3)N(4) photoelectrode, this strategy develops 2 orders of magnitude higher conductivity and 3 orders of magnitude longer-lived shallow-trapped charges. Furthermore, the average OCVD lifetime observed for def-g-C(3)N(4) is 5 times longer than that observed for g-C(3)N(4). Thus, clear photocathode behavior has been observed with negative photocurrent densities of around −10 μA/cm(2) at 0 V vs RHE. Open circuit photovoltage decay (OCVD), Mott–Schottky (MS) plot, and transient absorption spectroscopy (TAS) provide consistent evidence that long-lived shallow-trapped electrons that exist at about the microsecond time scale after photoexcitation are key to the photocathode behavior observed for defect-rich g-C(3)N(4), thus further demonstrating g-C(3)N(4) can be both a photoanode and a photocathode candidate.